The efficacy of accounts for a breach of confidentiality by management - Giacalone, Robert A.; Pollard, Hinda Greyser (1987)
Management and non-management employees of a northeastern bank read a description of a manager who engaged in a breach of confidentiality. Subjects were asked to evaluate the acceptability of 27 excuses. Results showed that subjects' ratings of acceptability were affected by their individual perception of the severity of the stimulus manager's breach of confidentiality. Subjects' rank did not affect acceptability of accounts.
Keywords: Northeastern Bank; Stimulus Manager; Individual Perception; Economic Growth